1984
DOI: 10.1080/00173138409427713
|View full text |Cite
|
Sign up to set email alerts
|

Variation of airspora in the atmosphere due to weather conditions

Abstract: A backnard-elimination, multiple-regression analysis was used to determine which metedrological factors significantly explained the variation measured in concentrations of allergenic spore forms 1.5 m above ground level. Airspora were collected for three years (19761978) with volumetric samplers. Adequate moisture is probably the most important variable in spore production. In the imperfect fungi, once the spores are produced, release is often influenced by wind velocity. In the Ascomycetes, radiation, minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 21 publications
5
32
0
2
Order By: Relevance
“…It was reported that light triggered fungal spores release in several fungi, and light was required to initiate ascopore discharge in many of the bitunicate fungi (Leach, 1975;Lyon et al, 1984;Li and Kendrick, 1994). The study of Salvaggio and Aukrust (1981) showed that conidia of Cladosporium and Alternaria were often abundant during midday periods with maximal sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that light triggered fungal spores release in several fungi, and light was required to initiate ascopore discharge in many of the bitunicate fungi (Leach, 1975;Lyon et al, 1984;Li and Kendrick, 1994). The study of Salvaggio and Aukrust (1981) showed that conidia of Cladosporium and Alternaria were often abundant during midday periods with maximal sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in relative humidity levels were found to affect fungal spore release of different fungal phyla. Rainfall affected positively the release and dispersal of Basidiomycetes (Lyon et al, 1984).…”
Section: Worldwide Relevant Aeromycological Studiesmentioning
confidence: 99%
“…Mean rainfall during the study period was the highest throughout the year, the spores of basidiomycetes are wet spores and their dispersal was mainly and directly affected by the precipitation (Lyon et al, 1984). Sufficient moisture, either during rainfall or when humidity increases is required for the spore production of Ganoderma (Ho et al, 2005;Stępalska & Wołek, 2009).…”
Section: Diurnal Variation Of Fungal Spore Populations In the Atmosphmentioning
confidence: 99%
“…La correlación positiva de la velocidad del viento ha sido puesta de manifiesto también por Burch & Levetin (2002) y por Calderón et al (1997). Sin embargo, Lyon et al (1984) encontraron una correlación negativa entre la velocidad del viento y la concentración de conidios. Hjelmroos (1993) mostró una correlación positiva con la temperatura y precipitación.…”
Section: Discussionunclassified